Twin-distortion modulated ultra-low coordination PtRuNi-Ox catalyst for enhanced hydrogen production from chemical wastewater - Yue Zhang; Xueqin Mu; Zhengyang Liu; Hongyu Zhao; Zechao Zhuang; Yifan Zhang; Shichun Mu; Suli Liu; Dingsheng Wang; Zhihui Dai (Nature Communications)
Abstract The development of efficient and robust catalysts for hydrogen evolution reaction is crucial for advancing the hydrogen economy. In this study, we demonstrate that ultra-low coordinated hollow PtRuNi-Ox nanocages exhibit superior catalytic activity and stability across varied conditions, notably surpassing commercial Pt/C catalysts. Notably, the PtRuNi-Ox catalysts achieve current densities of 10 mA cm−2 at only 19.6 ± 0.1, 20.9 ± 0.1, and 21.0 ± 0.1 mV in alkaline freshwater, chemical wastewater, and seawater, respectively, while maintaining satisfied stability with minimal activity loss after 40,000 cycles. In situ experiments and theoretical calculations reveal that the ultra-low coordination of Pt, Ru, and Ni atoms creates numerous dangling bonds, which lower the water dissociation barrier and optimizing hydrogen adsorption. This research marks a notable advancement in the precise engineering of atomically dispersed multi-metallic centers in catalysts for energy-related applications.